2014
DOI: 10.1007/s10147-014-0676-4
|View full text |Cite
|
Sign up to set email alerts
|

Perception and needs of reproductive specialists with regard to fertility preservation of young breast cancer patients

Abstract: RS recognize the need for FP in YBC patients and are willing to participate in their care. Affiliation of RS was related to a positive attitude to egg preservation. Various concerns regarding FP among RS indicate the need for evidence that supports the safety of FP, inter-disciplinary communication, and practice guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…From a patient's perspective, reasons precluding fertility treatment may include high financial costs not covered by insurance, 20 focusing on the cancer diagnosis and urgency of treatment, 21 more effort and stress to seeing additional specialists, 22 not understanding the subsequent fertility risk from treatment, 23 or belief that pregnancy will not be possible or may be unsafe. 24 Barriers from a clinician's perspective include limited knowledge of fertility preservation options and safety, having insufficient office time to discuss, 25 a patient's current lack of spouse/partner, 25 believing that younger age signifies the ability for ovaries to easily bounce back from treatment, 24 narrow focus on acute treatment planning without discussing long-term side effects, 26 or fear of cancer treatment delay. 27 Importantly, the FD may have actually taken place, however the patient was not interested in future fertility options and discussion was not documented in the chart as a pertinent negative.…”
Section: Discussionmentioning
confidence: 98%
“…From a patient's perspective, reasons precluding fertility treatment may include high financial costs not covered by insurance, 20 focusing on the cancer diagnosis and urgency of treatment, 21 more effort and stress to seeing additional specialists, 22 not understanding the subsequent fertility risk from treatment, 23 or belief that pregnancy will not be possible or may be unsafe. 24 Barriers from a clinician's perspective include limited knowledge of fertility preservation options and safety, having insufficient office time to discuss, 25 a patient's current lack of spouse/partner, 25 believing that younger age signifies the ability for ovaries to easily bounce back from treatment, 24 narrow focus on acute treatment planning without discussing long-term side effects, 26 or fear of cancer treatment delay. 27 Importantly, the FD may have actually taken place, however the patient was not interested in future fertility options and discussion was not documented in the chart as a pertinent negative.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to adult providers (61, 62), pediatric providers demonstrated a great deal of variability and biases around fertility preservation counseling. The fact that providers are influenced by a stated desire for parenthood is in contrast to many adolescents’ perception that fertility preservation is a means of preserving a future choice rather than a statement about parenting intention.…”
Section: Discussionmentioning
confidence: 99%
“…• Almost half of clinicians in one study reported that cancer is more important than childbirth, even when the patient is cancer‐free, 5 years post‐treatment …”
Section: Methodsmentioning
confidence: 99%
“…Attitudes: A lack of consideration of FP, a moral objection to offer sperm banking in certain circumstances, a responsibility to decide on behalf of the patient, a belief that success rates of female FP were too low to justify, FP was too expensive for female patients, feeling anxious about treating fertility in breast cancer patients or concerned about unknown risk of cancer reoccurrence (with higher concern linked to male clinician status, private clinic vs hospital setting, and partner or parent status of the clinician) …”
Section: Methodsmentioning
confidence: 99%